DEVELOPMENT OF IRRIGATION NETWORK INFRASTRUCTURE IN SIRAPIT DISTRICT FOR FOOD SECURITY IN LANGKAT REGENCY - Heri Setiawan; Abdi Sugiarto; Cut Nuraini (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to examine the influence of irrigation network infrastructure development on food security in Sirapit District, Langkat Regency. Through a qualitative approach, this study explores the role of irrigation in supporting agricultural productivity and the stability of local food supply. The results of the study indicate that the existence of a good irrigation network significantly increases cropping intensity and production efficiency, and reduces the risk of crop failure. However, the effectiveness of the irrigation system still faces various obstacles such as physical damage, weak community participation, and lack of water management technology. Therefore, collaboration between the government and the community and technological innovation are important strategies in realizing food security based on sustainable irrigation management.